KONSTRUKSI MODEL HUBUNGAN DUA VARIABEL DENGAN ANALISIS REGRESI SPLINE - Yozza, Hazmira; Afrimayani, Afrimayani (Sainstek : Jurnal Sains dan Teknologi, 2019)
This paper discussed about the construction of a model the relationship between a dependent variabel and a independent variabel using spline analysis regression.  This methods is usually used when the relationship between variables is unknown.  This methods is applied to construct the growth curve for children under 3 years of age in Padang.